Keadilan untuk Komunitas: Perspektif Politik Komunitarianisme Michael Sandel - Hamudy, Nurul Annisa (Research and Development Agency Ministry of Home Affairs, 2020)
The ideals of justice are failing, with the widespread violence and discriminatory acts against various communities in Indonesia, despite what Michael Sandel's view that the community's view of good and fair was formed based on the community's beliefs about what is considered as good and fair. Community has an important role in communal living, since each community has a range of values ​​and concepts of good. As such, the concept of a good society cannot simply be derived from the general principle but need to be obtained through the exploration of the community’s values ​​and beliefs. For this reason, this study aimed to review the communitarianism-style of justice in the philosophical perspective of Michael Sandel. Using descriptive and documents analysis methods, as well as qualitative approaches, the results of the study showed that justice can be created from the promotion of value. Through a consensus, it is hoped that the government can explore the community’s value to be a mutual guideline in community living. This value can be accepted as a common good. Justice in society can only be sensibly created if it starts with the agreed and shared insights. Therefore, justice, according to Sandel, can only be created by using shared community values.